Ethical, legal and social aspects of human cerebral organoids and their governance in Germany, the United Kingdom and the United States - Pichl, Anja; Ranisch, Robert; Altinok, Ozan Altan; Antonakaki, Melpomeni; Barnhart, Andrew J.; Bassil, Katherine; Boyd, J. Lomax; Chinaia, Alice Andrea; Diner, Sarah; Gaillard, Maxence; Greely, Henry T.; Jowitt, Joshua; et al. (Frontiers in Cell and Developmental Biology, 2023)
Human cerebral organoids (HCOs) are model systems that enable researchers to investigate the human brain in ways that had previously been impossible. The emergence of HCOs was accompanied by both expert and layperson discussions concerning the possibility of these novel entities developing sentience or consciousness. Such concerns are reflected in deliberations about how to handle and regulate their use. This perspective article resulted from an international and interdisciplinary research retreat “Ethical, Legal and Social Aspects of Human Cerebral Organoids and their Governance in Germany, the United Kingdom and the United States”, which took place in Tübingen, Germany, in August 2022. The retreat focused on whether HCO research requires new ethical and regulatory approaches. It addressed epistemic issues around the detection and theorisation of consciousness, ethical concerns around moral status and research conduct, difficulties for legislation and guidelines managing these entities, and public engagement.